Whole‐genome analysis identifying candidate genes of altitude adaptive ecological thresholds in yak populations. (7th May 2019) - E, Guang‐Xin; Basang, Wang‐Dui; Zhu, Yan‐Bin
Abstract: The domestic yak ( Bos grunniens ) is an iconic symbol of animal husbandry on the Qinghai–Tibet Plateau. Long‐term domestication and natural selection have led to a wide distribution of yak, forming many ecological populations to adapt to the local ecological environment. High altitude is closely related to oxygen density, and it is an important environmental ecological factor for biological survival and livestock production. The aim of the present study was to perform a preliminary analysis to identify the candidate genes of altitude distribution adapted ecological thresholds in yak using next‐generation sequence technology. A total of 15, 762, 829 SNPs were obtained from 29 yaks with high‐ and low‐altitude distribution by genome‐wide sequencing. According to the results of the selective sweep analysis with FST and ZHp, 21 candidate genes were identified. 14 genes (serine/threonine protein kinase TNNI3K, TEN1, DYM, ITPR1, ZC4H2, KNTC1, ADGRB3, CLYBL, TANGO6, ASCC3, KLHL3, PDE4D, DEPDC1B and AGBL4) were grouped into 32 Gene Ontology terms, and four genes (RPS6KA6, ITPR1, GNAO1 and PDE4D) annotated in 35 pathways, including seven environmental information processing and one environmental adaptation. Therefore, the novel candidate genes found in the current study do not only support new theories about high‐altitude adaptation, but also further explain the molecular mechanisms of altitude adaptation threshold in yaks.